The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1038/clpt.1994.3
|View full text |Cite
|
Sign up to set email alerts
|

Debrisoquin oxidation genotype and susceptibility to lung cancer

Abstract: The association between the polymorphism of the cytochrome P450 debrisoquin hydroxylase (CYP2D6) and lung cancer is controversial. Previous reports suggested a link between CYP2D6 phenotype and lung cancer, with poor metabolizers having reduced susceptibility. Nevertheless, negative findings have also been published. By using allele-specific amplification, we have studied the frequency of four CYP2D6 (wild type and mutant) alleles in 89 patients with histologically proved bronchogenic carcinoma and in 98 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…EM would be more exposed than EIM and PM to genotoxic porphyrinogenic xenobiotic metabolites. Several authors have presented similar results in different studies performed with lung cancer and urinary bladder cancer patients (22)(23)(24). Agündez et al (25) observed a significant correlation between EM and the risk of liver cancer development.…”
Section: Discussionsupporting
confidence: 65%
“…EM would be more exposed than EIM and PM to genotoxic porphyrinogenic xenobiotic metabolites. Several authors have presented similar results in different studies performed with lung cancer and urinary bladder cancer patients (22)(23)(24). Agündez et al (25) observed a significant correlation between EM and the risk of liver cancer development.…”
Section: Discussionsupporting
confidence: 65%
“…CYP2D6*9 alleles, which were present at an increased frequency among lung cancer patients in a previous study from our group [13], were also more frequent among the newly analyzed 31 lung cancer patients. Global frequencies were: lung adenocarcinoma (15%), small-cell lung cancer (8%), and epidermoid lung cancer (13%).…”
Section: Resultsmentioning
confidence: 70%
“…There were 96 patients with larynx cancer and 103 patients with lung cancer. Seventy-two lung cancer patients have been studied for point mutations in the CYP2D6 gene in a previous study [13]and for gene deletion and duplication in the present study. All patients were evaluated by consultant physicians, and the diagnosis was based on histological analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the inclusion criteria, 43 studies (Agúndez et al, 1994;Wundrack et al, 1994;Agúndez et al, 1996;Ladona et al1996;Legrand et al, 1996;London et al, 1997;Agúndez et al, 1998;Febbo et al, 1998; González et al, 1998; Hu et Shaw et al, 1998;Krajinovic et al, 1999;Lemos et al, 1999;Topić et al, 2000;Butler et al, 2001;Liu et al, 2002;Sobti et al, 2003;Chen et al, 2004;Fukatsu et al, 2004;Li et al, 2004;Gajecka et al, 2005;Gomes et al, 2005;Guo et al, 2005;Liang et al, 2005;Mochizuki et al, 2005;Sobti et al, 2005;Aydin-Sayitoglu et al, 2006;Bonanni et al, 2006;Li et al, 2006;Lemos et al, 2007;Chen et al, 2008;Khedhaier et al, 2008;Majumdar et al, 2008;Ouerhani et al, 2008 ;Torresan et al, 2008;Yan et al, 2008;Altayli et al, 2009;Gutman et al, 2009;Lim et al, 2011;Luo et al, 2011;Zhou et al, 2011) appeared to have met the inclusion criteria and were subjected to further examination. The flow chart of study selection is shown...…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%